2018
DOI: 10.1002/ece3.4647
|View full text |Cite
|
Sign up to set email alerts
|

Rebel honeybee workers have a tendency to become intraspecific reproductive parasites

Abstract: Worker honeybees may reproduce in either their own or foreign colonies; the latter situation is termed intraspecific reproductive parasitism (IRP). In this study, we compared the tendency for IRP between normal honeybee workers, which are characterized by a relatively low reproductive potential, and “rebel workers”, a recently discovered subcaste of honeybee workers characterized by a high reproductive potential that develops when the colony is without a queen. We expected that the high reproductive potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Thus, workers developing at larval stage in a queenless colony become relatively selfish individuals with higher reproductive potential than those that develop in a colony with a queen. These workers called rebel workers are characterized not only by their increased reproductive potential but also other altered anatomical features (e.g., less developed HGs, larger mandibular glands; [ 20 ]), shortened preimaginal development [ 22 ], prolonged life [ 23 ], different foraging preferences [ 24 ], tendency to drift to other colonies [ 25 ], increased sucrose sensitivity [ 26 ], energy reserves and protein concentrations in fat body [ 4 ], and increased learning ability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, workers developing at larval stage in a queenless colony become relatively selfish individuals with higher reproductive potential than those that develop in a colony with a queen. These workers called rebel workers are characterized not only by their increased reproductive potential but also other altered anatomical features (e.g., less developed HGs, larger mandibular glands; [ 20 ]), shortened preimaginal development [ 22 ], prolonged life [ 23 ], different foraging preferences [ 24 ], tendency to drift to other colonies [ 25 ], increased sucrose sensitivity [ 26 ], energy reserves and protein concentrations in fat body [ 4 ], and increased learning ability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have more ovarioles in their ovaries, as well as better developed mandibular glands and underdeveloped hypopharyngeal glands. Moreover, their ovaries are activated regardless of whether they live in queen-less or queen-right colonies [ 24 , 25 , 26 , 27 ]. Since the rebels are so anatomically and behaviorally different from the normal workers and more queen-like, the following questions arise: How do their gland cells function, and are they morphologically similar to the gland cells of queens or workers?…”
Section: Introductionmentioning
confidence: 99%
“…These workers are called rebel workers (M Woyciechowski and Kuszewska 2012), and studies have shown that these individuals lay eggs more often than normal workers, even if they remain in a colony with a queen (Karolina Kuszewska et al 2018c). Compared to normal workers, rebel workers are characterised not only by their increased reproductive potential but also by their prolonged life (Karolina Kuszewska et al 2017), different foraging preferences (Kuszewska et al 2018b), tendency to drift to other colonies (Karolina Kuszewska et al 2018a) and increased sucrose sensitivity (Karolina Kuszewska et al 2019).…”
Section: Introductionmentioning
confidence: 99%